2014
DOI: 10.1002/mde.2709
|View full text |Cite
|
Sign up to set email alerts
|

Network or Independent Business? Entrepreneurs' Human, Social and Financial Capital as Determinants of Mode of Entry

Abstract: When establishing a new business, entrepreneurs can decide to join a network of independent business partners rather than choose the alternative of independent business ownership. In this study, we use a probit model on a large database to study the human, social, and financial capital of French entrepreneurs who join franchising and comparable forms of networks. Results confirm that initial levels of human and social capital are significant determinants of network membership. We also show that an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
1
11
1
1
Order By: Relevance
“…We contribute to franchising research by enhancing scientific knowledge on the antecedents of individual intentions to become franchisees as a specific type of EI. Whereas, previous studies have shown the relevance of economic, strategic, and demographic variables in explaining individual EI regarding franchising (Bastié et al, 2016;Watson and Stanworth, 2006), our study demonstrates that motivational, and cognitive, variables are also relevant. The adoption of AMT, in combination with TPB, has proven fruitful in our study as our analysis of primary data on 666 individuals ('non-entrepreneurs') shows non-linear associations between motivation, on one hand, and cognitive assessment of franchising or EI regarding franchising, on the other hand.…”
Section: Theoretical Implicationscontrasting
confidence: 95%
“…We contribute to franchising research by enhancing scientific knowledge on the antecedents of individual intentions to become franchisees as a specific type of EI. Whereas, previous studies have shown the relevance of economic, strategic, and demographic variables in explaining individual EI regarding franchising (Bastié et al, 2016;Watson and Stanworth, 2006), our study demonstrates that motivational, and cognitive, variables are also relevant. The adoption of AMT, in combination with TPB, has proven fruitful in our study as our analysis of primary data on 666 individuals ('non-entrepreneurs') shows non-linear associations between motivation, on one hand, and cognitive assessment of franchising or EI regarding franchising, on the other hand.…”
Section: Theoretical Implicationscontrasting
confidence: 95%
“…Also, there is an indirect relationship between government policy (through Nigerian infrastructural development) and SME's financial aid and accessibility and employment generation (b = 0.52, 0.43; p < 0.05, supporting Ho7 and Ho8). The indirect impact shows that government policy has been very helpful in helping entrepreneurs gain access to financial aid and thereby creating more employment opportunities for youths in Nigeria (Bastiéa et al, 2016). The findings align with the work of Carsamer (2012) and Galindoa and Mendez (2014) as they found that the central bank of Nigeria's intervention on financial loans to SMEs in Nigeria has been a key support to business growth and employment creation in Nigeria.…”
Section: Hypotheses Testingsupporting
confidence: 75%
“…However, the added support and training may be perceived as favourable and maybe even necessary to the entrepreneur capable of acquiring and then managing the financial and knowledge-based capital needed to successfully navigate the added complexities of the franchise arrangement. Bastie et al (2016) support this contention in their findings that higher levels of both human and social capital, as measured by levels of education and familiarity with franchisees, are significant determinants of franchising.…”
Section: Human Capital Theorymentioning
confidence: 83%